Integración y transformación económica en África: potencial y limitaciones del Área de Libre Comercio Continental Africana - Eduardo Bidaurratzaga-Aurre; Artur Colom-Jaén; Ainhoa Marín-Egoscozábal (Revista Iberoamericana de Estudios de Desarrollo)
In March 2018, the African Union gave way to the establishment of the African Continental Free Trade Area, the largest area of economic integration in the world by number of countries involved. As of June 2020, 54 out of 55 African Union member countries have already signed the agreement, thus showing an almost complete unanimity on this topic. AfCFTA comes up when industrialisation strategies and economic transformation in Africa seem to have taken over orthodox structural adjustment and post-adjustment approaches. AfCFTA aims to increase the scarce intra-African trade, boost economic transformation, create the regional value chains and help African firms to join the global value chains. In this article, we analyse the AfCFTA potential as a tool for economic transformation strategies, and the difficulties of its implementation.